Adenocarcinoma of the Thymus, Enteric Type: Report of 2 Cases, and Proposal for a Novel Subtype of Thymic Carcinoma. (April 2015) - Moser, Bernhard; Schiefer, Ana Iris; Janik, Stefan; Marx, Alexander; Prosch, Helmut; Pohl, Wolfgang; Neudert, Barbara; Scharrer, Anke; Klepetko, Walter; Müllauer, Leonhard
Abstract : We report 2 cases of primary thymic adenocarcinoma with enteric differentiation. One carcinoma occurred in a 41-year-old man as a 7-cm-diameter cystic tumor and the other one in a 39-year-old woman as a 6-cm-diameter solid mass. Both tumors were located in the anterior mediastinum. Clinical staging did not reveal any extrathymic tumor. Histologically, the tumors were classified as adenocarcinoma, not otherwise specified, and a mucinous (colloid) carcinoma, respectively. Immunohistochemically, both tumors were positive for cytokeratin 20 (CK20), CDX2, and carcinoembryonic antigen, reflecting enteric differentiation. A review of the literature on 43 other cases of primary thymic adenocarcinomas suggested 11 further cases with enteric differentiation, as assessed by CK20 and/or CDX2 expression. We propose that thymic adenocarcinoma with enteric differentiation represents a novel subtype of thymic carcinoma. It is mostly of mucinous morphology and frequently associated with thymic cysts. The clinical outcome is variable. Recognition of primary thymic adenocarcinoma with enteric differentiation is helpful for the differentiation from metastatic disease, mainly from the gastrointestinal tract.